(untitled) (Environment & Health, 2016)
We identified the areas unfavorable for residing in the Transcarpathian region on the basis of the study of the peculiarities of the ecological situation in the region followed the cartography of their calculated physiological equivalence. Materials and methods. For the assessment of the ecological conditions of residing of the population we used the indices of the territorial concentration of production, commercial cultivation of land, population density, environmental contamination (chemical, air, natural water, soil and radiation), natural conditions (degree of territory damages by the adverse anthropogenic processes). Primary preparation for the systematization of the obtained data was performed with the help of Microsoft Excel. Results. Performed cartography of the study results showed a presence of high-risk areas in the Transcarpathian region where the living conditions of the population didn’t correspond to the existing sanitary-and-hygienic requirements. Medico-geographical analysis of etiopathogenetic intercommunication of the total contamination of the region (different risk degrees) with the definite nosologic forms of the diseases among the local population will be a subsequent stage of the study. Conclusions. Developed map may be used by the specialists in the sphere of medical geography, by the sanitary inspectors and interested bodies as a basis for the measures on the improvement of the ecological situation in the areas at risk. A problem of day is a unification of the efforts of the doctors, hygienists and other professionals, looking for alternative ways to ensure the population’s residing conditions whose quality corresponds to the physiological needs of a human.